Structural Gene Characterization And Development Of Real-Time Pcr Detection Method For Infectious Bronchitis Virus - Mohamed Zulperi, Zarirah (2008)
Infectious bronchitis virus (IBV) causes an acute, highly contagious disease that associated with significant economical losses to the poultry industry worldwide. Since IB vaccine induced immunity is serotype-specific, vaccine failures are often associated with the emergence of antigenic variants that differ from the vaccine viruses. Hence, structural genes characterization of IBV isolates is required for developing strategies to improve currently used vaccines. This study described the sequence analysis of structural genes S1, S2, M and N of two Malaysian IBV strains, MH5365/95 and V9/04. The structural genes were amplified using gene-specific primers in reverse-transcriptase polymerase chain reaction (RT-PCR) and cloned into TOPO TA cloning vector. The cloned products were then sequenced and complete nucleotide and amino acid sequences of the genes were determined and analyzed using bioinformatics tools. Nucleotide sequence alignments revealed many point mutations, short deletions and insertions in S1 region of both IBV strains. Sequence and phylogenetic analysis of S1 and M genes showed that MH5365/95 and V9/04 are variant strain since it does not relate to any Massachusetts vaccine strains of IBV. Analysis based on other structural genes (S2, M and N), indicated both strains are highly related to each other and there were less mutation occurred in the respective genes. A one step real-time PCR procedure using SYBR Green I dye was used in this study. The developed PCR was performed using a pair of newly designed primers against N gene. Amplification was detected when primer was used with vaccine strains, H120, Volvac® ND+IB MLV, Cevac® BI L, Poulvac® IB H-120, Cevac® Bron 120 L, Beaudette and M4 and non-vaccine strains, T-strain, MH5365/95 and V9/04 with TM ranging from 85.2°C to 86.0°C. The sensitivity of the assay was compared to the conventional method for IBV detection, virus isolation test using 18 clinical samples from IB suspected cases. Six out of 18 suspected IB cases were positive when analyzed using the real-time PCR assay while none of the samples showed consistent results through lesion observation when analyzed using the virus isolation method followed by HA test. Therefore, the SYBR Green I real-time PCR was found to be more sensitive than virus isolation method. In addition, it was found the assay could detect up to 1:103 dilution of RNA with the concentration 1X 10-1 ng/μl. The assay was also proven to be specific in IBV detection since no specific amplification signal was detected when tested avian viruses such as AIV H9N2, IBDV isolate MB067/05 and NDV isolate 00/IKS. Therefore, the study has successfully developed a rapid, sensitive and specific method for IBV detection using SYBR Green I based real-time PCR when compared to virus isolation and HA test. However, further experiment for improvement of the assay is needed to evaluate the reliability of the system in order to replace the traditional diagnostic method for IBV detection.